PEMBIASAAN SALAT DHUHA DALAM MEMBENTUK SIKAP DISIPLIN PESERTA DIDIK MADRASAH IBTIDAIYAH AL-KAUTSAR MAGELANG - Agusti Purwani; Isti Sufiana; Daryati Daryati; Fisti Sucia Ningrum; Naomi Fahma (STKIP Pesisir Selatan, 2026)
This study is motivated by the importance of developing students’ discipline as an essential aspect of character education in Islamic schools. MI Al-Kautsar Magelang implements a routine Dhuha prayer program to cultivate discipline through consistent practice, adherence to worship rules, and personal responsibility. This research aims to describe how the Dhuha prayer habituation is implemented, the forms of discipline developed among students, and the supporting and inhibiting factors influencing the program. This research employs a descriptive qualitative approach. The research subjects include the principal, teachers, and students. Data were collected through observation, in-depth interviews, and documentation. Data analysis followed Miles and Huberman’s model, consisting of data reduction, data display, and conclusion drawing. The results indicate that the habituation of Dhuha prayer is implemented systematically through teacher guidance, daily routines, and exemplary behavior from educators. The program contributes to shaping students’ discipline, particularly in time management, rule compliance, and consistent positive behavior. Supporting factors include a religious school environment, teacher commitment, and parental involvement.